A remuneraç\~ao de internaç\~oes e a tabela de procedimentos do SUS: Uma análise a partir do SIH e SIGTAP - Maria Angelica Borges dos Santos; Raulino Sabino da Silva; Rodrigo Pucci de Sá ce Benevides; Luciana Mendes Santos Servo (Instituto de Pesquisa Econômica Aplicada (IPEA), 2023)
– We explore variations in the values paid for Unified Health System (Sistema Único de Saúde - SUS) hospitalizations financed by the federal government according to procedures recorded in the SUS Hospital Information System (SIH) for the year 2019. We detail billing components (main procedures, special procedures and secondary procedures), type of financing (medium and high complexity ceiling - MAC ceiling - and Strategic Actions and Compensation Fund - Faec) and differences between procedure codes and nature of service flows. Our analysis showed a large variance in remunerations for identical procedure codes and different providers. We highlight the fact that, despite recurring criticisms concerning the Tabela SUS, only hospitalizations clearly linked to it allow a clear vision of remuneration criteria. Member states of Brazil finance little under half of SUS hospitalizations and, for these resources, the criteria of allocation is mostly unknown. Emphasis is also given to the implications of using linear readjustments of hospital fees, as well as to the discussion around the eventual adoption of Diagnosis Related Groups (DRGs). The findings of these analyzes may serve as a starting point for proposing improvements to the Tabela, including dialoguing with some of the proposals presented in the working group report about Tabela SUS.
Keywords: I18; 330; Unified Health System; fee schedules; hospital charges